A proposal to use Instagram in methodology applicable in High School disciplines (Research, Society and Development, 2019)
We propose the use of the Instagram application as a didactic resource in the teaching and learning process of the disciplines in the high school curriculum, without abandoning the original uses that characterize the application and which were socially constructed by its users. The proposal described aims to the use of the cellphone and the Instagram as a possible solution to the difficulties faced in contemporary teaching in front of the entrance of social media in the classroom, as cellphones are increasingly present and are used in a way considered inconvenient for the expected behavior of students in the classroom. The proposed method explores four functions of Instagram: Stories, Direct, IGTV e Post, which can be used at different times during or outside of classes. As result, the tool proved effective, meeting the proposed requirements for facilitating communication between students and teachers, as well in the dissemination of contents related to the topics discussed in the classroom in terms of ubiquitous learning, once the application can be accessed from anywhere and at any time, provided you have an internet connection. In conclusion, except restrictions of local normative character and internet access, the use of cellphones associated with the Instagram application, has potential attributes that can be exploited as an auxiliary tool of the teacher to make approach diagnoses appointed by him during the classes, as well as a virtual environment of extraclass communication, where the teacher has the possibility to provide content that favors the social and technological dynamics oriented to the acquisition of knowledge.